John Dewey e a educação como "reconstrução da experiência": um possível diálogo com a educação contemporânea - Carlesso, Dariane (2008)
This research was developed in the Education Post-Graduation Program / Mastership, at the Federal University of Santa Maria (PPGE/UFSM) and is linked to the Research Line: Education, Politics and Culture. The research had as a main objective to know the concept of experience present in John Dewey s work, in the expression education as construction and reconstruction of experience , which is his own concept. Through a bibliographical research in some of John Dewey s works about education, elements that characterize experience were delineated. The investigation also tried to understand and reflect, through current literature, about what characterizes the schooling culture nowadays, what are the conceptions that reinforce the students experiential culture in the school place. As the school is considered a place not only permeated, but also producer of culture besides producer of students experience valuing discourse, a study about the experience constituting paradigms was necessary. In this way, the school current condition among different difficult situations it is facing was questioned, especially by the separation of school knowledge and the students life. In order to cover the present-day educational discourses of experience valuing reported inside the school place itself, six teachers speeches, who work with children in public schools, were reflect about through semi-structured interviews. Such interviews were analyzed through the content and textual analysis technique and received an interpretation in order to comprehend what bases the concept of experience. In this sense, teaching, learning, student and teachers role present in teachers speeches conceptions were studied. When comparing Dewey s education conceptions and the experience characterizer element presented nowadays at school, this research concluded that we are still assented basically in a traditional education that, even though it proclaims itself as a supporter of experiences in the school place, it reduces this comprehension in just go there and do . And, when it affirms about knowing the students experiences, they are not faced as new construction possibilities, in the connected and continue sense of knowledge construction process. The most teachers speeches point to an experience dimension turned to living, immediate situations, practices, in the restricted sense of the terms. Considering it, however the students experience valuing is pronounced, the necessity and importance of bringing their lives to inside the school place, it is still done in a superficial way, without the inherent intention of an experience comprehension as a human improvement; that is, the experience and its continuous reconstruction as a process of knowledge construction. This impossibility of converging Dewey s concept of experience with what is pronounced in educational discourses nowadays is due to the lack of basis in what is being said in the present days.